Labor Decomposition Analysis Under New Technology of Legume Crops in Arid Zone of Rajasthan - Singh, Bahrat; Gajja, B L (Annals of Arid Zone, 2016)
The paper .attempts to define the factors showing the effects on output and use of labor in case of old and new technology along with complementary input components. The new technologies are supposed to increase economic growth by increasing productivity, efficiency and profitability. It was found that increases in labor employment due to adoption of new technology of moth bean and c1usterbean wcre 57.44 and 47.61%. respectively. It was further observed that the increase in employment was mainly due to technical changes which were 42.02 and 25.18% in moth bean and clusterbean. respectively. Therefore, it can be concludcd that modern technology adopted for cultivation of moth bean and clusterbean is supposed to increase thc cmploymcnt generation and agricultural production’ in the arid zonc of Rajasthan.